Evaluating the Effectiveness of Community Participation in Stunting Reduction in Surabaya - Sani, Yunni Maulidya; Hariyoko, Yusuf; Roisul Basyar, Muhammad (CV. Era Digital Nusantara, 2024)
Abstract: Stunting is a growth and developmental disorder in children caused by several factors, including poor nutrition, recurrent infections, and inadequate psychosocial stimulation. Children are considered stunted if their height-for-age is more than two standard deviations below the median of the Child Growth Standards. Despite efforts, stunting among children under five years old persists in Surabaya. Therefore, the Surabaya City Government, in collaboration with medical professionals, is actively working to treat and prevent stunting to achieve the goal of Zero Stunting in Surabaya. The role of the community is crucial in eradicating stunting among young children to foster a stunting-free golden generation in Surabaya. Purpose: The objective of this study is to describe the forms of community participation under Mayor Regulation No. 79 of 2022 concerning the Acceleration of Stunting Reduction in Surabaya. Design/Methodology/Approach: The research method employs a survey methodology to collect data. This study gathers information from primary sources, obtained directly from the surveyed subjects, and secondary sources, which include existing data and literature relevant to the research topic. Findings: The research findings indicate that community participation in Surabaya is present and commendable, although it is not yet fully optimal. While several participation indicators show positive results, such as participation in labor, material contributions, social involvement, and skills, there is still a need for improvement in the participation of ideas, particularly in providing input or suggestions related to stunting reduction programs. Therefore, increased community engagement is necessary to achieve the goal of Surabaya Zero Stunting. Originality/value: This study has several distinctions in terms of focus, theme, and research location. It will examine community participation within the context of Surabaya Mayor Regulation No. 79 of 2022 concerning the Acceleration of Stunting Reduction in Surabaya.